2007
DOI: 10.1590/s1806-83242007000500003
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the epidemiology of periodontal diseases in Latin America

Abstract: The aim of the present review was to identify the presence of periodontal diseases and the relative importance of known risk factors in Latin American countries. The retrieved data are sparse and inconsistent, lacking information for the majority of the countries. Gingivitis is ubiquitous in the region, affecting all ages independently of the socioeconomic background. The extension of bleeding may vary greatly, ranging from 40% to 70% of sites. The prevalence of aggressive periodontitis is higher in Latin Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 43 publications
1
18
0
9
Order By: Relevance
“…Cigarettes have also been shown to be the major risk factor in the prevalence, extent, and severity of periodontal diseases. 3,4,5,6 Some studies have demonstrated the possible absorption of nicotine by the root surfaces of smokers with periodontal disease. 7,8 In addition, fibroblasts that were exposed to nicotine Naida Zanini ASSEM (a) Márcio Luiz Ferro ALVES (a) Alessandra Barreto LOPES (a) Erivan Clementino GUALBERTO JUNIOR (a) Valdir Gouveia GARCIA (b) Letícia Helena THEODORO …”
Section: Introductionmentioning
confidence: 99%
“…Cigarettes have also been shown to be the major risk factor in the prevalence, extent, and severity of periodontal diseases. 3,4,5,6 Some studies have demonstrated the possible absorption of nicotine by the root surfaces of smokers with periodontal disease. 7,8 In addition, fibroblasts that were exposed to nicotine Naida Zanini ASSEM (a) Márcio Luiz Ferro ALVES (a) Alessandra Barreto LOPES (a) Erivan Clementino GUALBERTO JUNIOR (a) Valdir Gouveia GARCIA (b) Letícia Helena THEODORO …”
Section: Introductionmentioning
confidence: 99%
“…3 This process may ultimately result in the loss of the diseased teeth. 4 PD is a common oral health problem worldwide, and variations in its prevalence may originate from differences in methodology and diagnostic criteria: 5 whereas half of Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…1 Smoking is the major risk factor in the prevalence, extent and severity of periodontal diseases. [2][3][4][5] Cross-sectional studies have shown that smokers are two to seven times more likely to present periodontitis, compared to nonsmokers, 2,6,7 and smoking has been associated with tooth loss during periodontal maintenance as well. 7,8 With respect to surgical or non-surgical periodontal therapy, several studies have shown that smokers have a worse response to treatment when compared to nonsmokers.…”
Section: Introductionmentioning
confidence: 99%